An Analysis of Code Switching Used in Cinta Laura Khiel Podcast - Agus Wardhono; AyudyaTyosa Shendy Khatama (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2022)
Language is an activity that people do to express their feelings and the means to communicate with others in the daily activity primally in socializing with people around. This day many people already speak use two language or more where code switching also give a role in language changes. Code switching is not only found in the surrounding environment but also in an interview, social media, novels or a song. This time the writer focuses on Cinta Laura Khiel podcast with DeddyCorbuzier, Boy William, Chef Juna and AzkaCorbuzer. The purpose of this study is to know what is the dominant type and factor of code switching that appear in Cinta Laura Khiel podcast. This study is use qualitative descriptive method to collect the data. The writer use theory from Brown to analyze the type of code switching, the writer also use theory from Hoffman to analyze the factor of code switching, the most dominant type is inter-sentential switching with 173 data, the most dominant factor is repetition for clarification with 47 data.